Color in the Landscape: Finding Inspiration for a Color Theme - Gail Hansen; Erin Alvarez (EDIS)
ENH1164, a 4-page illustrated fact sheet by Gail Hansen and Erin Alvarez, describes different types of color schemes, properties of color, sources of inspiration, how to test color schemes, and varieties of texture and form. Published by the UF Department of Environmental Horticulture, June 2010.